Hot Times of Fencing - Lidin, Konstantin (project baikal, 2013)
The article attempts to identify a symbolical sense of the fence as an element of city semantics. Methods of the analysis of the sense of the word "fence" and its derivatives in Russian and the analysis of examples from architecture and town planning history are used.It is shown that the fence possesses not only a delimitative, but also offensive and aggressive sense. The fence means a border between different ways of life, each of which seeks to take away a vital space from the neighbor. The fence-wall literally divides sites with different structures of life. The fence-sign, the fence-notional border divides the areas protected from each other by the law. At last, the decorative and demonstrative fence not merely divides structures, but also expresses claims of one of them to be a model for another.Often the communities divided by a fence consider only their own way of life as something structured, ordered, natural and correct. The way of life existing "behind a fence" is perceived not as a different structure, but as an unstructured chaos. The more uncomprehended the alien structure is, the more chaotic and fearful it seems, and the higher and stronger the fences become.Like the majority of socio-psychological processes, the balance between uneasiness and trust has periodic oscillatory changes. In recent twenty years a strong growth of uneasiness and all related phenomena have been observed. Including the growth in the number, variety and aggressive activity of various fences.
Keywords: semantics of the city; architecture; town planning; city structure; fence; way of life; balance "uneasiness – trust"